Growth and quality of Handroanthus heptaphyllus (Vell.) Mattos. seedlings as a function of controlled release fertilizer doses - Souza, Adrielly Costa; Gama, Marcos André Piedade; Araújo, Dênmora Gomes; Silva, Gabriel Pinheiro; Vilhena Senado, Jéssy Anni (Revista Sustinere, 2020)
Controlled-release fertilizers are great allies in the production of seedlings. However, there is a lack of studies focusing on the use of these fertilizers in native forest species. This study aimed to evaluate the effect of different doses of controlled release fertilizers (CRF) on the development and quality of seedlings of Handroanthus heptaphyllus (Vell.) Mattos. The experiment was carried out under greenhouse conditions with plastic cover for a period of 150 days. The pots were distributed in randomized blocks, using twenty plants per experimental unit. The treatments consisted of four doses of CFR Osmocote® (0, 4.1, 8.2 and 12.3 g dm-3) in the formulation NPK 15-09-12, with four replications. The following variables were evaluated: seedling height (H), stem diameter (SD), root length (RL), number of leaf pairs (NLP), leaf area (LA), shoot dry mass (SDM), root dry mass (RDM), total dry mass (TDM), H/SD ratio, Dickson's quality index (DQI) and relative chlorophyll content (SPAD). All evaluated parameters responded significantly to the increasing doses of the CRF. The best responses were found for the doses between 8.5 to 9.5 g dm-3, considering the evaluated experimental conditions.